GAMBARAN KONSEP DIRI PASIEN KANKER PAYUDARA DI POLIKLINIK BEDAH RSUP DR. M. DJAMIL PADANG TAHUN 2013 - Yulastri -; Aini Yusrab; Novi Herawatic (Universitas Andalas, 2016)
Abstract   Breast cancer cause various psychological symptoms as a result of changes in body shape, uncertainty about the future, and the impact of recurrence of breast cancer treatment. As a result, many patients don't adhere to treatment. Negative self-concept is a response that is maladaptive adjustment. According to WHO the incidence increased every year, 6.25 million people in 2002. The aim of research to describe the concept of self-breast cancer patients at the Clinic Surgical Hospital Dr M Djamil Padang 2013. This research is descriptive, at the Polyclinic Hospital Surgery Dr. M Djamil Padang. Population is all of breast cancer patients who visited the Polyclinic Surgery amounted to 234 people. Accidental sampling as many as 49 people. Data were collected in July 2013 using a questionnaire and analyzed by univariate. Results of the study the majority (57.1%) of respondents have a positive body image. Most (57.1%) of respondents have a negative self ideal. General (75.5%) of respondents have a negative self-esteem. Most (53.1%) of respondents have a negative self-identity and most (51%) of respondents have a negative self role. Surgery Clinic nurses are expected to be able to conduct assessments of physiological stressors, self-concept in patients with breast cancer by providing health education and motivate patients to seek treatment until complete. As well as the need for cognitive therapy given by a nurse specialist mental patients with breast cancer to improve their quality of life.   Keyword        : cancer, breast cancer, self-concept   ABSTRAK   Kanker payudara menimbulkan berbagai macam gejala psikologis sebagai akibat perubahan bentuk tubuh, ketidakpastian tentang masa depan, kekambuhan serta dampak pengobatan kanker payudara. Akibatnya banyak pasien yang tidak patuh terhadap pengobatannya. Konsep diri yang negatif merupakan respon penyesuaian yang maladaptif. Menurut WHO setiap tahun kejadiannya meningkat, 6,25 juta orang pada tahun 2002. Tujuan penelitian untuk mengetahui gambaran konsep diri pasien kanker payudara di Poliklinik Bedah RSUP Dr M Djamil Padang pada tahun 2013. Penelitian ini bersifat deskriptif, di Poliklinik Bedah RSUP Dr. M Djamil Padang. Populasi adalah semua pasien kanker payudara yang berkunjung ke Poliklinik Bedah berjumlah 234 orang. Pengambilan sampel secara Accidental Sampling sejumlah 49 orang. Data dikumpulkan pada Juli 2013 menggunakan kuesioner dan dianalisis secara univariat. Hasil dari penelitian sebagian besar (57,1%) responden memiliki citra tubuh positif. Sebagian besar (57,1%) responden memiliki ideal diri negatif. Umumnya (75,5%) responden memiliki harga diri negatif. Sebagian besar (53,1%) responden memiliki identitas diri negative dan sebagian besar (51%) responden memiliki peran diri negatif. Diharapkan perawat Poliklinik Bedah dapat melakukan pengkajian stresor fisiologis, konsep diri pada pasien kanker payudara dengan memberikan pendidikan kesehatan dan memotivasi pasien untuk berobat sampai tuntas. Serta perlunya diberikan terapi kognitif oleh perawat spesialis jiwa bagi pasien dengan kanker payudara untuk meningkatkan kualitas hidupnya.   Kata kunci   : kanker, kanker payudara, konsep diri